Pulsatile Flushing: A Review of the Literature. Issue 1 (January 2019) - Boord, Christina
Abstract : Flushing is an essential strategy in maintaining patency of a central vascular access device. However, there is no standard practice regarding flushing techniques. Pulsatile flushing has been discussed in the past based on the principles of fluid dynamics. Recently, in vitro studies regarding pulsatile flushing have shed light on the usefulness of this technique. A critique of the current literature regarding pulsatile flushing compared with standard continuous flushing is presented here.